Kecenderungan Pesan Budaya Fotografi Human Interest: Analisis Isi Karya Fotografi Human Interest Pada Akun Instaggram @Okyarisandi - Imam Ali (Brand Communication, 2023)
Human interest photography works often contain a message or deep meaning in each of them. This is influenced by the involvement of humans in this photographic work as a condition for photographic works to be called human interest types of photographic works. This study aims to determine the trend of human interest photography culture messages on the Instagram account @Okyarisandi. This study uses content analysis, with quantitative methods, to determine the trend of human interest photography culture messages on the Instagram account @Okyarisandi. The results showed that a total of 100% of the samples tested had been adjusted to several predetermined categories. Researchers get results where Human Interest photography works on the Instagram account @Okyarisandi tend to be in the Livelihoods category. Which reached a percentage of 57.5%